2019
DOI: 10.5114/aoms.2018.73856
|View full text |Cite
|
Sign up to set email alerts
|

Flow-mediated dilation can be used to predict incident hypertension in patients with hyperuricemia

Abstract: IntroductionThe aim of the study was to evaluate whether flow-mediated dilation (FMD) can be used to predict incident hypertension in patients with hyperuricemia.Material and methodsNormotensive participants with and without hyperuricemia at baseline were prospectively enrolled. Flow-mediated dilation was assessed at baseline, and after 1 year’s follow-up the incidence of hypertension was compared between those with and without hyperuricemia. The predictive value of baseline FMD for incident hypertension among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Another arterial parameter, FMD, which is used to determine an endothelial dysfunction, showed no relationship with SUA in our study. Only several small studies have been performed on this topic, and the findings are controversial [ 37 , 38 , 39 ]. Some authors hypothesized that FMD may be an early predictor of vascular dysfunction, and including patients with coronary artery disease and/or diabetes may lead to a diminished difference between normouricemic and hyperuricemic patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another arterial parameter, FMD, which is used to determine an endothelial dysfunction, showed no relationship with SUA in our study. Only several small studies have been performed on this topic, and the findings are controversial [ 37 , 38 , 39 ]. Some authors hypothesized that FMD may be an early predictor of vascular dysfunction, and including patients with coronary artery disease and/or diabetes may lead to a diminished difference between normouricemic and hyperuricemic patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study on systemic lupus erythematosus showed that the accumulation of damage in patients was associated with a progressive loss of FMD, with preserved endothelium-independent vasodilation [ 41 ]. Han et al [ 42 ] found that low baseline FMD in hyperuricemia patients was associated with a significantly increased risk of incident hypertension and that FMD could be used as one of the predictive factors of the risk of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Оскільки в результаті дослідження виявлений прямий негативний зв'язок середньої сили між рівнем сечової кислоти та ендотелійзалежної вазодилятації, можна говорити про негативний вплив гіперурикемії на ендотеліальну дисфункцію у пацієнтів з АГ. Останні дослідження також підтверджують, що пацієнти з гіперурикемією мають підвищений ризик розвитку АГ, а низький базовий рівень ендотелійзалежної вазодилятації у пацієнтів з гіперурикемією без АГ пов'язаний з підвищеним ризиком розвитку АГ [4].…”
Section: обгоровенняunclassified
“…Зокрема, сечова кислота розглядається як один із чинників, що впливає на судинну жорсткість [3]. У пацієнтів з коморбідністю гіперурикемії та АГ спостерігаються прояви ендотеліальної дисфункції, а низький базовий рівень ендотелійзалежної вазодилятації у пацієнтів з гіперурикемією без АГ є предиктором розвитку АГ [4]. Таким чином, існує необхідність подальшого вивчення взаємозв'язків між гіперурикемією та іншими модифікованими факторами ризику АГ.…”
unclassified